Putin and Russia in retro and forward: the nuclear dimension. Issue 1 (2nd January 2017) - Cimbala, Stephen J.
ABSTRACT: Deterioration in security relations as between NATO and Russia reached boiling point in the aftermath of Russia's annexation of Crimea in 2014 and its subsequent destabilization of Eastern Ukraine. As a result, some voices in the West look forward to the departure of Vladimir Putin from power, and others to the possible disintegration of Russia as a unitary state. However, both the departure of Putin and the collapse of Russia have a nuclear dimension. Putin has issued pointed reminders of Russia's status as a nuclear great power, and Russian military doctrine allows for nuclear first use in the event of a conventional war with extremely high stakes. Beyond Putin, a breakup of Russia would leave political chaos in Eastern Europe, Central Asia and elsewhere, inviting ambiguous command and control over formerly Russian nuclear forces.